Modularity analysisof users’mobile behavior in campus wireless network - Chang-ling ZHOU; Qun QIAN; Yi-qiu ZHAO; Qun SHANG (Tongxin xuebao)
Choosing a better and easily computed similarity metric is a challenge task,and the problem how the formedmodularity can help network operation attracts less attention.By introducing sparse linked interval(SLI) to represent wireless nodes' mobile trajectory,mobile nodes' modularity relations via social network analysis methods were effectively revealed.Using real operational datasets of Peking University campus wireless network and public dataset as validation,three common motifs in modularity level,and their formation reasonsand relations to network managements were demonstrated.